مجلة دراسات في التاريخ والاثار 71: العالم والمحدث والامام الـعابد عبد الله بن المبارك المتوفى( سنة 181 هــ - 797 م ) - عمران, وفاء عبد الجبار (مجلة دراسات في التاريخ والآثار, 2020)
الملخص Conclusion         Khurassan and Marrow are considered the most famous Islamic cities  for their scholars and sciences and they both became a passage for the other countries  around  the world  .Thus, Abdullah bin Al-Mubarek was one of those scholars who was characterized  by his social ,ethical, scientific, and cultural   traits in his life. Such an apathetic scholar and a generous man had suffered much in his life's stages from childhood till old age ,but he kept on struggling till he managed to become an educated person .          Abdullah bin Al-Mubarek was one of the modernizers who was a remarkable figure in Prophetic Tradition as admitted by other scholars and jurists .Such status reached by this scholar resulted  from instructing from other sheiks , and later on had his own countless number of students to the degree that he was highly praised by famous poets in his time .